Emotional Intelligence and Organisational Commitment of Lecturers at Kyambogo University - Kimata Kato, Joshua; Mugizi, Wilson; Kyozira, Peter; Kasule, George Wilson (Interdisciplinary Journal of Sociality Studies, 2023)
The study examined the casual link between emotional intelligence and organisational commitment of lecturers at Kyambogo University. Specifically, the study examined the link between the four emotional intelligence competencies of self-awareness, self-management, social awareness, and relationship management with organisational commitment of full-time lecturers at Kyambogo University. The three-component model of organisational commitment by Allen and Meyer, which describes it in terms of affective, normative, and continuance commitment, was used to assess the concept. Using the correlational research design, the study adopted the quantitative approach. The study participants were 175 fulltime lecturers of the selected university. The data were collected using a self-administered questionnaire. Structural equation modelling (SEM) using SmartPLS was used to analyse the data. The study findings indicated that while self-management and social awareness were significant determinants of organisational commitment of full-time lecturers, relationship management and self-awareness were positive but insignificant determinants of organisational commitment. The study concluded that while selfmanagement and social awareness are essential for the organisational commitment of lecturers, relationship management and self-awareness are not. Therefore, it was recommended that to promote the organisational commitment of lecturers, university managers should take cognisance of lecturers' self-management and social awareness more than relationship management and self-awareness.
Keywords: Affective; Continuance; Normative; Relationship-management; Self-awareness; Selfmanagement; Social-awareness